2017
DOI: 10.1002/pits.22089
|View full text |Cite
|
Sign up to set email alerts
|

Promoting sisterhood: The impact of a culturally focused program to address verbally aggressive behaviors in Black girls

Abstract: New estimates report that Black girls are facing an educational crisis with regard to disproportionate disciplinary practices and academics. To date, there has been very limited research with regard to school-based interventions that have been designed to help Black girls explore both their cultural and gender identity. This is problematic because Black girls are constantly faced with the task of disproving negative characterizations (i.e., angry, loud, and aggressive) and advocating for equitable treatment fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…In other studies, interventions were designed to be culturally relevant including Sisters of Nia and Brothers of Ujima which teach about Afrocentric values and identity. For Sisters of Nia, authors found strong effect sizes for participants' perceptions of social strengths in one study and decreases in verbal aggression in another (Aston et al, 2017). For Brothers of Ujima, strong effect sizes were noted for social resiliency (Graves & Aston, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…In other studies, interventions were designed to be culturally relevant including Sisters of Nia and Brothers of Ujima which teach about Afrocentric values and identity. For Sisters of Nia, authors found strong effect sizes for participants' perceptions of social strengths in one study and decreases in verbal aggression in another (Aston et al, 2017). For Brothers of Ujima, strong effect sizes were noted for social resiliency (Graves & Aston, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Sisters of Nia is one of those interventions that focus on teaching 5 th grade African American girls about their cultural values and beliefs in order to increase their racial identity [51]. By the end of the program, African American girls had built strong connections with other members within the group, and positive behavior change was reported for all participants [26]. Jernigan [52] implemented a mentoring intervention called Sankofa to help African American girls to increase racial and gender identity.…”
Section: Discussionmentioning
confidence: 99%
“…These types of masculine behaviors, as George defines them, are seen as unnaturally strong [5]. Unfortunately, when African American girls violate gender norms or traditional expectations, they are penalized for these actions in ways that are not the same for white girls [26]. For example, when African American girls show assertiveness, it is often misunderstood as being confrontational, and they are punished harshly for it [7].…”
Section: African American Girlsmentioning
confidence: 99%
“…Other changes could incorporate an intersectional perspective into the learning environment. Scholars have noted that promoting strong, positive views of racial identity is one way to support Black girls and counter negative school experiences (Ashton, Graves, McGoey, Lovelace, & Townsend, 2018;Winn, 2013). For example, Winn (2013) describes her program of "Restorative English Education" as a means to use subject matter and classroom experiences to promote dialogue, understanding of lived experiences, and collaboration between teachers and students.…”
Section: Moving Forward With Black Girls In Mindmentioning
confidence: 99%